Choruses in Attic Vase-Painting of the 6th–5th Centuries BC - Kulishova, Oksana V.; Karpyuk, Sergey G. (Actual Problems of Theory and History of Art, 2017)
The authors analyze some characteristics of ancient Greek vase-painting in order to study ancient drama and theatre. This problem has been discussed a lot within the last decades, e.g. in the works of J. R. Green,O. Taplin, E. Csapo et al. The authors focus on the Attic vase-painting of the 6th–5th centuries BC, which was close to the time of ancient Greek theatre to be born. The group of Attic vases with the so-called ‘animal’ choruses (ca. 560–480 BC) draws the scholars’ attention due to nearly twenty pictures of costumed processions offantastic birds, cocks, horsemen, riders on dolphins, etc. These sets remind of ‘animal’ choruses in Aristophanes’The Birds and The Knights. The authors specially analyze the so-called ‘rider choruses’ on the Greek vases from the museums of Berlin, Boston, New York, etc. All these pictures help to prove socio-cultural (and not onlyreligious!) aspects of komos. This analysis also allows the authors to discover sources of ancient Greek comedy and dramatic performances, which were connected with aristocratic culture of symposion in Archaic and early Classical Greece.